Extracurricular Activities for Enhancing Proficiency in English Language Learning: A Comprehensive Analysis (2023)
As a compilation monograph, this study discusses extracurricular activities, specifically focusing on learning English to enhance language acquisition. The primary aim of this research endeavor is to contribute to developing effective pedagogical practices rooted in extracurricular activities within the context of English language teaching. The central objective is to discern and elucidate the advantages and merits of diverse extracurricular activities designed to bolster English language learning in educational institutions, encompassing schools and universities.